Identification of Runs of Homozygosity Islands and Genomic Estimated Inbreeding Values in Caqueteño Creole Cattle (Colombia) - Toro-Ospina, Alejandra M.; Rios, Ana C. Herrera; Schettini, Gustavo Pimenta; Aristizabal, Viviana H. Vallejo; Santos, Wellington Bizarria dos [UNESP]; Zapata, Cesar A.; Morea, Edna Gicela Ortiz (MDPI, 2022)
The Caqueteño Creole (CAQ) is a native breed of cattle from the Caquetá department (Colombia), adapted to tropical conditions, which is extremely important to production systems in those regions. However, CAQ is poorly studied. In this sense, population structure studies associated with runs of homozygosity (ROH) analysis would allow for a better understanding of CAQ. Through ROH analysis, it is possible to reveal genetic relationships between individuals, measure genome inbreeding levels, and identify regions associated with traits of economic interest. Samples from a CAQ population (n = 127) were genotyped with the Bovine HD BeadChip (777,000 SNPs) and analyzed with the PLINK 1.9 program to estimate FROH and ROH islands. We highlighted a decrease in inbreeding frequency for FROH 4–8 Mb, 8–16 Mb, and >16 Mb classes, indicating inbreeding control in recent matings. We also found genomic hotspot regions on chromosomes 3, 5, 6, 8, 16, 20, and 22, where chromosome 20 harbored four hotspots. Genes in those regions were associated with fertility and immunity traits, muscle development, and environmental resistance, which may be present in the CAQ breed due to natural selection. This indicates potential for production systems in tropical regions. However, further studies are necessary to elucidate the CAQ production objective.
Keywords: cattle native; inbreeding; tropical